Client and Clinician Experiences and Perspectives of Exercise Physiology Services During the COVID-19 Pandemic: Qualitative Study - Riley C C Brown; Shelley E Keating; Patrick J Owen; Paul S Jansons; Jenna McVicar; Christopher D Askew; Kelly M Clanchy; Ralph Maddison; Andrew Maiorana; Suzanne M Robinson; Niamh L Mundell (JMIR Publications, 2023)
BackgroundThe COVID-19 pandemic led to changes in the delivery of exercise physiology services. The lived experience of those who continued to provide or receive exercise physiology services during the heightened public health restrictions of the inaugural year of the COVID-19 pandemic has received little attention to date. Acquiring this knowledge will be fundamental in addressing whether telehealth is a viable option for service delivery in exercise care, research, and policy. This is especially pertinent in the wake of the COVID-19 pandemic and subsequent global interest in digital health delivery of health care services. ObjectiveThis study aims to explore the clinician and client experiences and perspectives of exercise physiology services delivered in person or via telehealth during the inaugural year of the COVID-19 pandemic (after January 25, 2020; the date of the first confirmed case in Australia). MethodsEligible participants for this study were adult (aged 18 years or older; capable of understanding and writing in English) clients who received and clinicians who delivered 1 or more exercise physiology sessions in Australia during the first year of the COVID-19 pandemic (June 2020 to June 2021). The data collection period spanned from January 20, 2021, to September 24, 2021. A total of 18 semistructured individual interviews were conducted with accredited exercise physiologists (n=7) and clients (n=11) who engaged with exercise physiology services during this period. All interviews were digitally recorded and transcribed verbatim. Thematic analysis was conducted with themes and subthemes derived using deductive and inductive approaches. ResultsA total of 3 dominant themes, each with 2 subthemes, were identified. The first theme was that telehealth enables access to services but limits the use of some clinical tools. Remote access to services was valued by both clinicians and clients, but the exercise clinical environment could not be replicated over telehealth. This was especially true regarding access to exercise equipment. Second, engagement and the "relational space" are limited by telehealth. Perceived challenges regarding social interactions and a sense of community were a limitation for clients, and difficulties fostering clinician-client report were noted by clinicians. Finally, technological challenges are pervasive in the telehealth delivery of exercise services. Both clinicians and clients noted that systems necessary to facilitate telehealth frequently disrupted delivery, and client-based technical issues were influenced by digital health literacy. ConclusionsShared client and accredited exercise physiologist experiences highlight key considerations for the ongoing implementation of telehealth to facilitate the uptake and effectiveness of exercise physiology services. These findings imply that the co-design of solutions to client-perceived limitations of telehealth delivery is warranted.